K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

28 tháng 6 2023

\(3x\ge0\)

\(\Leftrightarrow x\ge\dfrac{0}{3}\)

\(\Leftrightarrow x\ge0\)

Vậy: ...

2 tháng 4 2017

1.\(3x^2+12x-66=0\)

\(\Rightarrow\)\(3\left(x^2+4x+4\right)-78=0\)

\(\Rightarrow3\left(x+2\right)^2=78\)

\(\Rightarrow\left(x+2\right)^2=26\)

\(\Rightarrow x+2=\sqrt{26}\)hoặc \(x+2=-\sqrt{26}\)

\(\Rightarrow x=\sqrt{26}-2\)hoặc \(x=-\sqrt{26}-2\)

12 tháng 12 2015

9x2 +4x2 =20xy =>\(\int^{9x^2-12xy+4y^2=8xy}_{9x^2+12xy+4y^2=32xy}\Leftrightarrow\int^{\left(3x-2y\right)^2=8xy}_{\left(3x+2y\right)^2=32xy}\Leftrightarrow\frac{\left(3x-2y\right)^2}{\left(3x+2y\right)^2}=\frac{1}{4}=A^2\)

A>0 => A =1/2

27 tháng 11 2021

Answer:

\(B=\left(2x+1\right)^2+\left(3x-1\right)^2+2.\left(2x+1\right).\left(3x-1\right)+5\)

\(=[\left(2x+1\right)^2+\left(3x-1\right)^2+2.\left(2x+1\right).\left(3x-1\right)]+5\)

\(=[\left(2x+1\right)+\left(3x-1\right)]^2+5\)

\(=\left(2x+1+3x-1\right)^2+5\)

\(=\left(5x\right)^2+5\)

\(=25x^2+5\)

17 tháng 8 2019

\(x\left(3x-5\right)-9x+15=0\)

\(\Leftrightarrow x\left(3x-5\right)-3\left(3x-5\right)=0\)

\(\Leftrightarrow\left(x-3\right)\left(3x-5\right)=0\)

\(\Leftrightarrow\orbr{\begin{cases}x-3=0\\3x-5=0\end{cases}}\Leftrightarrow\orbr{\begin{cases}x=3\\x=\frac{5}{3}\end{cases}}\)

17 tháng 8 2019

\(3x\left(x-5\right)-2\left(5-x\right)=0\)

\(\Leftrightarrow3x\left(x-5\right)+2\left(x-5\right)=0\)

\(\Leftrightarrow\left(3x+2\right)\left(x-5\right)=0\)

\(\Leftrightarrow\orbr{\begin{cases}3x+2=0\\x-5=0\end{cases}}\Leftrightarrow\orbr{\begin{cases}x=\frac{-2}{3}\\x=5\end{cases}}\)

5 tháng 1 2021

3x2 + 3x - 5( x + 1 ) = 0

<=> ( 3x2 + 3x ) - 5( x + 1 ) = 0

<=> 3x( x + 1 ) - 5( x + 1 ) = 0

<=> ( x + 1 )( 3x - 5 ) = 0

<=> x + 1 = 0 hoặc 3x - 5 = 0

<=> x = -1 hoặc x = 5/3

5 tháng 1 2021

cảm ơn bạn nhiều nha

25 tháng 4 2018

2x . (3x - 4) - 6x + 8 = 0

<=> 6x2 - 8x - 6x + 8 = 0

<=> 6x- 6x - (8x - 8) = 0

<=> 6x (x - 1) - 8 . (x - 1) = 0

<=> (6x - 8) . (x - 1) = 0

<=> \(\orbr{\begin{cases}6x-8=0\\x-1=0\end{cases}}\Leftrightarrow\orbr{\begin{cases}x=\frac{8}{6}=\frac{4}{3}\\x=1\end{cases}}\)